Correction: The multifaceted nature of antimicrobial peptides: current synthetic chemistry approaches and future directions. (22nd December 2021) - Gan, Bee Ha; Gaynord, Josephine; Rowe, Sam M.; Deingruber, Tomas; Spring, David R.
Abstract : Correction for 'The multifaceted nature of antimicrobial peptides: current synthetic chemistry approaches and future directions' by Bee Ha Gan et al., Chem. Soc. Rev., 2021, 50, 7820–7880, DOI: ; 10.1039/D0CS00729C .